Evaluation of the effects of the black mulberry extract against Diazinon induced hepatotoxicity in albino wistar rats. - Javed, Safiya; Kalhoro, Raima; Memon, Shahnaz Bano; Zeeshan, Nabeela; Shaikh, Abdul Majid; Baloch, Ghulam Hussain (International Journal of Endorsing Health Science Research, 2021)
Background: Diazinon is the globally used organophosphorus compound to which humans are exposed through contamination of food and water. Flavonoids in Morus nigra exhibit a wide range of antioxidant, antimicrobial, anti-inflammatory, anti-cancer, anti-radiation properties and have a protective action against oxidative damage and hepatoprotective effects. The study's objective was to evaluate the effects of black mulberry (Morus nigra) extract against diazinon-induced hepatotoxicity in albino Wistar rats. Methodology: A quasi-experimental study was conducted from August 2019 to January 2020 at the Department of Pathology, Isra University, Hyderabad, Pakistan. Under standard colony conditions, thirty-six healthy male albino Wistar rats weighing between 200 and 300 grams were randomly divided equally into three groups: Group-1 (Control), Group-2 (given 60 mg/kg Diazinon daily for 4 weeks), Group-3 (administered Diazinon 60 mg/kg with 500 mg/kg of Morus nigra extract daily for 4 weeks through orogastric intubation). Hepatic tissue of all groups was observed under the light microscope. At the same time, hepatic serum markers were also analyzed. Results: A statistically significant decline in the bodyweight and rise in absolute liver weight of group-3 compared with groups-1 and group-2 (p<0.05). Co-administration of Morus nigra significantly lowered serum AST ad ALT levels. Significant histopathological derangement was observed in group-2 hepatic tissues while group-3 rats hepatic tissues had minimal changes and near-normal hepatic parenchyma. Conclusion: Morus nigra leaf extract has hepatoprotective effects against Diazinon-induced hepatotoxicity in male albino Wistar rats.